2022
DOI: 10.3390/ijerph192113952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Professional Values on Attitudes towards Professional Ethics in Future Physical Therapy Professionals

Abstract: This study aimed to analyze the influence of professional values on attitudes towards professional ethics, as well as the influence of sociodemographic variables on attitudes and professional values in future physical therapy professionals. A total of 231 physical therapy students (53% women; mean age 22.30 (SD = 5.13 years; age range 18–49)) participated. Attitudes towards professional ethics (Attitudes Questionnaire towards Professional Ethics in Physical Therapy) and professional values (Axiological Estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Marqués-Sule et al 59 argue that the teaching of ethics should be established in each year of the university degree, even if it is transversal in each subject. Ethics is a fundamental pillar in the clinical training of physiotherapy students, and as Moreno-Segura et al 60 say, the human sensitivity of physiotherapy students should be explored to shape the design of ethics training in the physiotherapy curriculum, as ethics training undoubtedly also serves to train future professionals in patient safety 61 . Aguilar-Rodríguez et al 59 reinforce the idea of the importance of ethics training for future physiotherapists, as it will enable them to identify situations in clinical practice in which bioethical principles may be violated in patient care during their clinical training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marqués-Sule et al 59 argue that the teaching of ethics should be established in each year of the university degree, even if it is transversal in each subject. Ethics is a fundamental pillar in the clinical training of physiotherapy students, and as Moreno-Segura et al 60 say, the human sensitivity of physiotherapy students should be explored to shape the design of ethics training in the physiotherapy curriculum, as ethics training undoubtedly also serves to train future professionals in patient safety 61 . Aguilar-Rodríguez et al 59 reinforce the idea of the importance of ethics training for future physiotherapists, as it will enable them to identify situations in clinical practice in which bioethical principles may be violated in patient care during their clinical training.…”
Section: Introductionmentioning
confidence: 99%
“…Aguilar-Rodríguez et al 59 reinforce the idea of the importance of ethics training for future physiotherapists, as it will enable them to identify situations in clinical practice in which bioethical principles may be violated in patient care during their clinical training. As Marques-Sule et al 61 concluded, in general, future physiotherapists attach great importance to ethics training and its impact on their professional training. Ethical awareness is related to safety in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals clinical practice and quality of care of patients may be influenced by ethical aspects, such as ethical and moral sensitivity, that could affect their daily clinical practice. In this sense, ethics currently has an important role in healthcare professions and especially in the physical therapy field [1][2][3][4][5][6]. It is expected that healthcare professionals have extensive intellectual and practical education to commit themselves to the welfare of those in their care [7].…”
Section: Introductionmentioning
confidence: 99%